The Advantage of Moringa oleifera Powder Addition in Natural Polymer Modified Concrete Mixture - Rr. M. I. Retno Susilorini; Budi Santosa; VG. Sri Rejeki; M.F. Devita Riangsari; Yan’s Dianaga Hananta (G-SMART, 2017)
Polymer modified concrete has become innovative materials to increase durability and sustainability of concrete. It is now important to develop natural polymers that are ‘greener’ than other chemical polymers. Therefore, this research wants to investigate compressive strength of natural polymer modified concrete added with Moringa oleifera powder, with and without its skin. This research was conducted experimentally in laboratory. There three compositions concrete mixture of several concrete cylinder specimens with dimension 10 cm x 20 cm which were cured in plain water for 7, 14, and 28 days. Compressive strength of normal concrete were designed as about f’c = 30 MPa. All specimens were tested for compressive strength after curing. This research meets conclusions: (1) Natural polymer modified concrete added by Moringa oleifera with skin specimens have compressive strength 82.85% compared control specimens; (2) Extreme high compressive strength has achieved by natural polymer modified concrete added by Moringa oleifera without skin specimens that have compressive strength 165,2% compared control specimens; and (3) Natural polymer made of Moringa oleifera is proven to increase the compressive strength of concrete